Business strategies in contexts of high uncertainty : a case study on the innovation and internationalization processes of a technological Portuguese SME - Barbosa, Fernando (2013)
Innovation and internationalization of small and medium enterprises are widely cited as decisive factors, for the sustainable growth of European economies, which are facing a deep crisis. The European Union launched in March 2010 a European strategy, called Europe 2020, to prepare the EU economy for the future, where growth is based in three dimensions: smart, sustainable and inclusive. In the Portuguese case, these factors become even more relevant, since the country is facing an unprecedented crisis that brought to the surface the vulnerabilities of its economic and financial system. This article is a case study of a small Portuguese technology based firm, where we will examine, in the light of the literature on strategic management, and the evaluation and selection of technologies, its innovation and internationalization processes, which are critical to its survival in a hypercompetitive global industry. The evaluation of new ideas and business concepts is a challenge for companies, especially in its early stages of development where there is not a tangible commercial product. This organization is launching a worldwide pioneering product, as a result of its research and development and innovation activities, and will have, if things go right, a huge successful impact on their competitiveness. The identification of the organizational characteristics that enabled the company to enhance its innovative stance, and to embrace the challenge to internationalize its activities, may help similar organizations improve their innovation and internationalization processes, which are critical to increase their competitiveness.